Kemampuan Komponen Arus Kas untuk Memprediksi Dividen Masa Depan - Reni Farwitawati (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2015)
Cash flow statement is a report that provides information about the company's cashreceipts and payments during a certain period. The report is useful to the ability of acompany to obtain a net cash inflows in the future, estimating the company's ability to paydebt and dividends, to evaluate the company's need for external financing, equalize thedifference between net income reported in the cash and non-cash from investing activitiesand financing during the period. Cash flow statement explains changes in cash a companyduring the period. When companies invest in short-term investments are highly liquid, thereport describes the changes during the period in terms of cash and equivalents. Theresearch looked at the components of cash flow ability to predict future dividends. Theresults showed operating cash inflows and outflows surgery can predict future cash flows